The Influence of Organizational Culture and Characteristics of Management Accounting Information System on Managerial Performance - Ayke Nuraliati; Septian Kusnaedi (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2023)
Organizational culture can influence the actions and decisions of managers, including choices about control systems. Therefore, organizational culture will affect the nature and habits of employees to improve performance effectiveness. Therefore, organizational culture needs to be developed in such a way as to increase the effectiveness of information systems, which will have an impact on the quality of information. Furthemore, Management accounting information systems help managers carry out their roles in planning, controlling and decision-making activities. Managers use management accounting information to identify and resolve problems and evaluate performance.This study aims to examine the effect of organizational culture and characteristics of management accounting information system on managerial performance. The object of this research is PT. Global Quality Indonesia located Kopo Mas Regency, Bandung City.This study uses a survey method with the number of respondents employees and managers. The data used in this study is primary data and uses a data collection method using a questionnaire. The results of the study are 1) Organizational culture has an effect on managerial performance. 2) Characteristics of management accounting information systems on managerial performance.